Effect of glucose and ascorbic acid on total phenolic content estimation of green tea and commercial fruit juices by using Folin Ciocalteu and Fast Blue BB assays - Roslan, Ahmad Syazrin; Ando, Yoshito; Azlan, Azrina; Ismail, Amin (Universiti Putra Malaysia Press, 2019)
Folin Ciocalteu (FC) assay had been widely used in the estimation of total phenolics content (TPC) in foods. However, the main disadvantage of this assay is that the reagent reacts with reducing substances and measures the total reducing capacity of a sample, not just phenolic compounds. The Fast Blue BB (FBBB) assay is another assay that can be used to estimate the total phenolic content in foods instead. The aim of the study was to estimate and compare the total phenolic content of green tea and commercial fruit juices using FC and FBBB assays, and also the effects of glucose and ascorbic acid on both assays. Green tea had the highest ascorbic acid content and TPC value among the samples. TPC estimated using FC assay were significantly higher than FBBB assay in all the samples. FC and FBBB assays were not affected by glucose at different concentrations. However, FC assay was significantly affected by the presence of ascorbic acid compared to FBBB assay. In conclusion, FC assay overestimated the TPC value in the sample extracts and was significantly affected by the presence of ascorbic acid. The FBBB assay can be considered as an alternative for estimation of total phenolic content in ascorbic acid-rich foods.